2009
DOI: 10.1089/ten.tea.2007.0280
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber Enabled Layer-by-Layer Approach Toward Three-Dimensional Tissue Formation

Abstract: Taking rapid and efficient formation of functional tissues as our long-term goal, we discuss in this study a new and generic approach toward formation of multilayered three-dimensional (3D) tissues using nanofibers. 3:1 poly (epsilon-caprolactone) (PCL) (8% w/v)/collagen (8.0% w/v) solution was electrospun into nanofibers with an average diameter of 454.5 +/- 84.9 nm. The culture of human dermal fibroblasts (NHDF) on PCL/collagen nanofibers showed a high initial cell adhesion (88.1 +/- 1.5%), and rapid cell sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 50 publications
0
125
0
Order By: Relevance
“…These scaffolds were found conducive to fibroblast growth and proliferation. Yang et al 152 created a layered structure of polymers and cells by electrospinning PCL and collagen together, seeding human dermal fibroblasts, and then repeating the polymer and cell layers. These cellularized constructs were done in sheet form and not with tubes.…”
Section: B Multilayer and Mixed Electrospinningmentioning
confidence: 99%
“…These scaffolds were found conducive to fibroblast growth and proliferation. Yang et al 152 created a layered structure of polymers and cells by electrospinning PCL and collagen together, seeding human dermal fibroblasts, and then repeating the polymer and cell layers. These cellularized constructs were done in sheet form and not with tubes.…”
Section: B Multilayer and Mixed Electrospinningmentioning
confidence: 99%
“…[ 1 ] Due to their dimensional similarity to the native tissue extracellular matrix (ECM), electrospun matrices have been explored for versatile applications in regenerative medicine aiming to promote cell-fi ber interactions for regulation of cell phenotype, [ 2 ] direct tissue regeneration via contact guidance, [ 3 ] support stem-cell proliferation and differentiation, [ 4 ] and create three-dimensional (3D) tissues with cells encapsulated inside the fi bers [ 5,6 ] or embedded among the fi bers. [ 7 ] …”
mentioning
confidence: 99%
“…Yang et al explored a 3-D multilayered cell-nanofiber scaffold with alternating layers of human dermal FBs or keratinocytes seeded on PCL/collagen nanofibrous sheets. The results indicated that both kinds of cells seeded could effectively proliferate and contribute to the formation of new ECM, which would indicate the potential to be a substitute of the skin [51] .…”
Section: Electrospun Nanofiber Scaffoldsmentioning
confidence: 94%